2020
DOI: 10.1186/s12955-020-01290-7
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and extent of self-care practice among heart failure patients in Ethiopia

Abstract: Background: Heart Failure (HF) results in an immense impact on the patients' Health-related quality of life (HRQOL). Heart failure patients HRQOL is dependent on the patients' level of engagement in self-care behaviors. Therefore this study aimed to determine HF patients' health-related quality of life and its relationship with self-care behaviors. Methods: An institutional-based study was conducted on 284 heart failure patients at the University of Gondar referral hospital. The data were collected using a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 39 publications
8
33
1
Order By: Relevance
“…We found significant correlations with generic and disease-specific quality of life dimensions on the KCCQ and with NYHA functional class and BNP level. These correlations, even though not very strong, support SCHFI v.7.2 validity because prior studies have shown that better self-care is associated with better patient quality of life (Seid, 2020;Vellone et al, 2017), a decrease in BNP level (Moon et al, 2018), and better functional class (lower NYHA; Vellone et al, 2017). Indirectly, the results of this study further support our premise that self-care improves patient outcomes.…”
Section: Construct Validitysupporting
confidence: 85%
“…We found significant correlations with generic and disease-specific quality of life dimensions on the KCCQ and with NYHA functional class and BNP level. These correlations, even though not very strong, support SCHFI v.7.2 validity because prior studies have shown that better self-care is associated with better patient quality of life (Seid, 2020;Vellone et al, 2017), a decrease in BNP level (Moon et al, 2018), and better functional class (lower NYHA; Vellone et al, 2017). Indirectly, the results of this study further support our premise that self-care improves patient outcomes.…”
Section: Construct Validitysupporting
confidence: 85%
“…In our study, we found that individuals with heart failure had low quality of life. Similar results have been obtained in other studies [32,33].…”
Section: Discussionsupporting
confidence: 93%
“…Both of these concepts have unique interrelationships in HF patients. Adequate self‐care behaviour positively impacts QoL, while a higher QoL can also increase the ability to perform HF self‐care adequately (Asadi et al, 2019; Seid, 2020). Based on this interrelationship, an intervention that can manage both concepts that may be needed, and nurse‐led telecoaching has the opportunity to manage it.…”
Section: Introductionmentioning
confidence: 99%